Successful Treatment of Recalcitrant Granuloma Gluteale Infantum with Topical Tacrolimus 0.03% Ointment - Alexander K. C. Leung; Kin Fon Leong; Joseph M. Lam (Hindawi Limited, 2021)
Granuloma gluteale infantum is a rare complication of irritant contact dermatitis. For the treatment of granuloma gluteale infantum, the diaper area should be kept clean and dry and the source of skin irritation should be removed or mitigated. For those infants who fail to respond to the conservative management, the use of topical calcineurin inhibitors should be considered. We report the successful treatment of a 12-month-old infant with recalcitrant granuloma gluteale infantum with the use of topical tacrolimus 0.03% ointment. To our knowledge, this is the second case reporting the use of topical calcineurin inhibitors in the treatment of recalcitrant granuloma gluteale infantum.